If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 5 + 2n + -8n Combine like terms: 2n + -8n = -6n 23 = 5 + -6n Solving 23 = 5 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. 23 + 6n = 5 + -6n + 6n Combine like terms: -6n + 6n = 0 23 + 6n = 5 + 0 23 + 6n = 5 Add '-23' to each side of the equation. 23 + -23 + 6n = 5 + -23 Combine like terms: 23 + -23 = 0 0 + 6n = 5 + -23 6n = 5 + -23 Combine like terms: 5 + -23 = -18 6n = -18 Divide each side by '6'. n = -3 Simplifying n = -3
| 3x+10=2(4x+50) | | 16=4m+4 | | -7y=14x | | -9=-4x-5x | | 8+3x=2x | | -8x+20y+4x^2=7-4y^2 | | 0=x^2+22x+112 | | 4(g+2)=2(4-g) | | -9=-x-5x | | c=8*3.14ab | | 6-6y=2(-3x+4) | | 23=-3r+6+2 | | -3x+3-4x=17 | | 4x^3=a*6x^5 | | 3=x+(-9) | | -(-3x-5)-(4x+2)=3 | | 6x+8-3x=20 | | -71=x+7x+9 | | X+45+45+40=180 | | (X+8)32=49 | | -8-7z=7-7z | | 3x+5y+7x-8= | | 5(y-6)+17=-33 | | 2x-10+7x=35 | | xz=10x+20 | | -(4x-2)=-(6x+4) | | 84+3x^2=x^2 | | (c-10)=-3 | | 5x+13=8x+1 | | x^2+2x+2=10 | | 6x+3+6x=-93 | | 2x-10y=44 |